How Well Does Google Translate, Translate from English to Indonesian? - Farida Repelita Waty Kembaren; Jauharah Jilan Situmorang; Liyundzira Fikroh Gani (Jurnal Pendidikan dan Sastra Inggris, 2024)
The aim of this study is to use matching techniques and language mistake analysis to figure out how accurate Google Translate is, especially when translating text from English to Indonesian. As a source text, one passage from Johann Gottfried Herder's book "Selected Writings on Aesthetics" was used to gather information. After that, Google Translate (GT) changes the info. When you look at GT translation data, you have to explain the matching technique and compare it with tools that measure the amount of translation matching. This way, mistakes in the language can be found and the quality of the GT translation can be judged. The study found that (1) out of the 13 source data, only 4 data (or 31%) are accurate translations, 7 data (or 54%) are less accurate translations, and 2 data (15%) are incorrect translations. right on. This means that the accuracy is only 31%. About half of it is less clear at the same time. Some people are hard to understand. (2) It turns out that GT can do good translations if it only uses literal translation and matching methods. (3) Since GT only uses textual and transposition translation strategies, it might make translations less accurate if more complicated strategies use transposition, modulation, or description together. (3) But if only a modulation technique is needed, GT can't do anything but make wrong translations. It doesn't make sense because it can only use the translation approach. Because it used a direct translation approach, GT failed to translate one case and made a translation that was wrong. In the end, Google Translate can only correctly translate English text into Indonesian when it uses a literal matching approach. This is especially true in this case.